STATE OF METABOLIC INDICES IN PATIENTS WITH GASTROCANCEROGENESIS AND THEIR DIAGNOSTIC VALUE - Васильєва, І.М.; Красносельський, М.В.; Жуков, В.І.; Вінник, Ю.О. (World of Medicine and Biology, 2015)
According to numerous publications, a steady increase in cancer incidence has been observed in recent years. In many cases it is accompanied by the abnormal clinical course of the disease. Early detection of malignancy and appropriate therapeutic measures are capable to prevent the development of complications of gastrocancerogenesis and prolong 5-year survival of patients. In the world there are many opinions regarding its etiology and pathogenesis. The most common view is scientific hypothesis about the numerous abnormalities of signaling, regulatory and integrative metabolic, cellular systems, providing adequate plastic, energy, proliferative and differentiation processes, whose changes can lead to malignant transformation of cells. The state of monitoring metabolic parameters in serum of patients with gastrocancerogenesis was studied and prognostic criteria of the severity of the disease and effectiveness of pathogenetic treatment were substantiated. This article is devoted to the study of monitoring metabolic indices for assessing impairments of homeostatic functions of the organism in 44 gastric cancer patients aged from 43 to 68 years with different stages of tumor development. Patients with gastrocancerogenesis had elevated levels of AsAT, AlAT, γ-GT, AP, CPK, CPK MB, and LDH in blood serum. The study of monitoring metabolic parameters in patients with gastrocancerogenesis showed reduction in glucose, urea, creatinine, total protein, albumin, cholesterol and elevation of triacylglycerol in plasma. The development of gastrocancerogenesis leads to significant impairments of protein, lipid, carbohydrate and mineral metabolism that are cooperatively linked to dysfunction of various organs and tissues and suppression of bioenergetic processes.